CAKAR AYAM PENDIDIKAN MUHAMMADIYAH - Eko Harianto (Universitas Muhammadiyah Ponorogo, 2017)
Study this library gives an overview of the educational characteristics of Muhammadiyah. Education in Muhammadiyah has based its own distinctive compared to education in General. Through this research note that chicken claw Muhammadiyah is a response to the education policy of the Government in the implementation of the curriculum that is applied. The integration of the system and the results of education that combine Islamic Science and general knowledge is philosophical thinking as well as the educational vision of Muhammadiyah.